Hadith #564 - Sunan Ibn Majah - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Lbabh bint al-Harith Trwa An لبابة بنت الحارث; Qabus bin Abi al-Makharq/al-Makharq قابوس بن أبي المخارق; Smak bin Hrb bin Aws سماك بن حرب بن أوس (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) used to lead us for the Zuhr, and we would hear him reciting a Verse after the Verses from Surat Luqman (31) and Adh-Dhariyat (51).”
Grade: